Effect of carbon fibre on properties of TiB2/C composite cathode coating for aluminum electrolysis - Li, Jie; Lü, Xiao-jun; Lai, Yan-qing; Li, Qing-yu; Tian, Zhong-liang; Fang, Zhao (Journal of Central South University of Technology. Science & technology of mining and metallurgy, 2008)
The tensile strength, compressive strength and electrical resistivity of TiB 2 /C composite cathode coating were measured with a hydraulic pressure universal test machine and an electrical resistivity test device, and the effects of carbon fibre content and carbon fibre length on tensile strength, compressive strength and electrical resistivity were investigated. The results show that the tensile strength of coating increases at the beginning and then reduces with the increase of carbon fibre content when the carbon fibre (length of 3 mm) content ranges from 0 to 4.0%; at the carbon fibre content of 1.5%, the tensile strength of coating reaches the maximum, 25.6 MPa. For the coating with carbon fibre content of 1.5%, the carbon fibre length has a great influence on tensile strength and compressive strength of coating; when the carbon fibre length is 6 mm, the tensile strength and compressive strength of coating reach the maximum, 27.6 MPa and 39.2 MPa, respectively. The electrical resistivity of coating reduces with the rise of temperature and the length of carbon fibre, and the influence of carbon fibre length on electrical resistivity of coating at low temperature (30–200 °C) is more obvious than that at high temperature (960 °C).